2021
DOI: 10.1039/d1nj01360b
|View full text |Cite
|
Sign up to set email alerts
|

Pt distribution-controlled Ni–Pt nanocrystals via an alcohol reduction technique for the oxygen reduction reaction

Abstract: Alloying Pt with transition elements as electrodes in fuel cells has been proposed to solve the CO poisoning effect besides cost-benefit. Consequently, the use of Ni-Pt nanoparticles (NPs) has been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The merit of the alcohol reduction method is that the reduction kinetics can be tuned by selecting the alcohol type and temperature and has been demonstrated in the synthesis of crystal phase, nanostructure, and shape-controlled synthesis of Cu-based bimetallic such as Cu–Ni, Co–Cu. , Our previous study suggested that the reduction potential of alcohols could be ranked in the following sequence by the theoretical calculation and experiment: 1-octanol > 1-heptanol > 1-hexanol ≫ 1-pentanol ≫ 1-butanol. Thus, in this section, we focused on the effects of the alcohol type for the Cu–Pd crystal phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The merit of the alcohol reduction method is that the reduction kinetics can be tuned by selecting the alcohol type and temperature and has been demonstrated in the synthesis of crystal phase, nanostructure, and shape-controlled synthesis of Cu-based bimetallic such as Cu–Ni, Co–Cu. , Our previous study suggested that the reduction potential of alcohols could be ranked in the following sequence by the theoretical calculation and experiment: 1-octanol > 1-heptanol > 1-hexanol ≫ 1-pentanol ≫ 1-butanol. Thus, in this section, we focused on the effects of the alcohol type for the Cu–Pd crystal phase.…”
Section: Resultsmentioning
confidence: 99%
“…Further, due to the difference in the initial reduction rates of metal, the internal structure of the metal particles could be tuned from a single crystal, singly twinned, multiply twinned, and further to stacking fault-lined, and the overall structure of the bimetals could be core–shell or alloy. The recent advances in the synthesis of metallic alloy nanostructures have proven that the use of the alcohol reduction method is a powerful choice to control the crystalline phase of metal/alloy NPs such as Cu–Co and Co–Ni systems by tuning the reduction kinetics and timing. In addition, the synthesis of transition–noble metallic NPs such as Ni–Pt, Co–Pt, and Ni–Pt–Pd was also reported. …”
Section: Introductionmentioning
confidence: 99%
“…In order to further increase Pt utilization while retaining the activity-enhancing effect of Ni, Ni@Pt and NiPt@Pt core@shell or ternary core@shell@shell ,, structures of various shapes have been synthesized. Again, core@shell structures with the {111} facets like octahedra, either synthesized by dealloying ,, or direct synthesis, , were prioritized, while some cubes , of ternary core@shell@shell nanoparticles were reported.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] In addition, despite the number of reports, the one-pot synthesis of low Pt alloy NPs with controlled composition and elemental distribution and the comparison of their catalytic properties have been hardly reported. 36,37 Hence, NiPt structured alloy NPs with only 26% Pt content have been found to exhibit higher mass and specific activities compared to other compositions. 37 However, the durability of these particles in the acidic environment was poor.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Hence, NiPt structured alloy NPs with only 26% Pt content have been found to exhibit higher mass and specific activities compared to other compositions. 37 However, the durability of these particles in the acidic environment was poor. Coating these particles with a thin layer of Pt, in other words, synthesis of NiPt alloy (core)-Pt(shell) NPs, successfully suppressed the dissolution in acidic media, 37 and their mass and specific activities improved from 5 to 8.0 and 2.7 to 9 times, respectively, when compared with commercial Pt catalysts.…”
Section: Introductionmentioning
confidence: 99%